Speedwell (Schooner : 1808) certification - Speedwell (Schooner : 1808)
Certification for the schooner Speedwell engaged in trade between Baltimore, Md., and Guadeloupe.
Collection material in French.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Ship's papers -- 19th century; Baltimore (Md.) -- Commerce; Gaudeloupe -- Commerce